2015
DOI: 10.1111/1751-7915.12266
|View full text |Cite
|
Sign up to set email alerts
|

Culture‐dependent and culture‐independent characterization of potentially functional biphenyl‐degrading bacterial community in response to extracellular organic matter from Micrococcus luteus

Abstract: Biphenyl (BP)-degrading bacteria were identified to degrade various polychlorinated BP (PCB) congers in long-term PCB-contaminated sites. Exploring BP-degrading capability of potentially useful bacteria was performed for enhancing PCB bioremediation. In the present study, the bacterial composition of the PCB-contaminated sediment sample was first investigated. Then extracellular organic matter (EOM) from Micrococcus luteus was used to enhance BP biodegradation. The effect of the EOM on the composition of bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 38 publications
0
17
0
3
Order By: Relevance
“…Overall, at the phylum level, the 10 isolates can be divided into three groups 1, 2 and 3 which belonged to Proteobacteria , Firmicutes and Actinobacteria respectively. Strains in group 1 belonged to Gram‐negative bacteria, which were well supported by the studies that Rpf also resuscitated and stimulated the growth of some Gram‐negative bacteria (Su et al ., ,b, ,b,c,d). In particular, ZS2R8 was closely related to uncultured bacterium clone FW2_72B () which was detected at low‐level waste site with cellulosic contaminants (Field et al ., ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Overall, at the phylum level, the 10 isolates can be divided into three groups 1, 2 and 3 which belonged to Proteobacteria , Firmicutes and Actinobacteria respectively. Strains in group 1 belonged to Gram‐negative bacteria, which were well supported by the studies that Rpf also resuscitated and stimulated the growth of some Gram‐negative bacteria (Su et al ., ,b, ,b,c,d). In particular, ZS2R8 was closely related to uncultured bacterium clone FW2_72B () which was detected at low‐level waste site with cellulosic contaminants (Field et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, our previous studies found that extracellular organic matter (EOM) from M . luteus containing the Rpf could stimulate and resuscitate uncultured bacteria belonging to phylum Actinobacteria (Su et al ., ,b,c,d). Therefore, the results of these cultivation studies are in line with the resuscitating and stimulating functions of Rpf on cellulose‐degrading bacteria in the compost sample.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations